USER SATISFACTION ON FACILITIES AND MAINTENANCE SERVICES OF STRATIFIED RESIDENTIAL BUILDINGS IN MALAYSIA - Nor Zaimah Che-Ghani,; Myeda, Nik Elyna; Azlan Shah Ali, (Journal of Surveying, Construction and Property, 2023)
This paper aims to investigate the performance of facilities and maintenance services provided in the four cases around Klang Valley for medium-cost stratified residential buildings. The quantitative methodology was adopted via questionnaire surveys to 137 residents of the four residential case study buildings. The analyses are frequency of failure, performance indicator by Weighted Average Satisfaction index (WAS) for the attributes: waiting time request and response from staff, professionalism and expertise of staff, worthiness of paid maintenance fee and relative performance index (RPIa) for the overall satisfaction for each facility as well as correlation test. Residents of the case studies were satisfied as the attributes of the performance recorded the WAS score of 40-79. The value of RPIa is closer to 1.00, indicating that almost all the facilities contribute to the good performance of the buildings and indirectly enhance the residents’ well-being. There is also a strong relationship between each attribute as the value of correlation is above 0.5 except for certain attributes in Case B. The present study suggests that maintenance services and facilities of residential buildings particularly should be in good condition and under proper care to enhance the performance of the buildings and the residents’ well-being. The study also noted that end user behaviour together with well-planned and functional management also contributes to the performance of the buildings.